Penerapan Model Pembelajaran Picture Word Inductive Model (PWIM) Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Kelas IV SD Muhammadiyah 5 Palembang - Lala Avriani; Mardeli Mardeli; Ibnu Rozali (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research is motivated by the low student learning outcomes, which are caused by a monotonous classroom atmosphere, limited facilities, lack of variety in teaching techniques, and the use of less appropriate methods. To overcome these issues, teachers need to implement a learning model that can create an active and enjoyable learning environment, such as the Picture Word Inductive Model (PWIM). This study aims to improve student learning outcomes in Islamic Religious Education (PAI) among fourth-grade students at SD Muhammadiyah 5 Palembang through the Picture Word Inductive Model (PWIM). Using a quantitative experimental method with a one-group pretest-posttest design, the sample consisted of 22 fourth-grade students from a population of 131. The results showed a significant improvement in learning outcomes, with the average pretest score rising from 57 to 90 in the posttest. A significance test yielded a p-value of 0.001 (p < 0.05), indicating a significant difference before and after using the PWIM model. These findings confirm that PWIM is an effective strategy for enhancing student learning in PAI.